The world economy moves at a gentler pace - Günter Großer; Günter Weinert (Intereconomics, 1990)
1989 was another highly satisfactory year for the industrialised countries, with real gross national product growing by an average of around 31/2%. Performance differed from one country to another, however, with the USA beginning to lag behind. Is this the harbinger of a general slowdown in growth?
Keywords: 330; Economic Trends